Methane adsorption characteristic dependency on zeolite structures and properties - Kamarudin, K. S. N.; Hamdan, H.; Mat, H. (2003)

(untitled)
Adsorption of methane on zeolites constitutes a new area of research since it has industrial importance in process industries such as natural gas purification and adsorptive natural gas storage. In this study, the dependency of methane adsorption characteristics on zeolite structure and properties was investigated. Zeolite framework was modified by cation exchange with different alkali metals. The incorporation of metal cations into zeolite structures changes their physicochemical properties. The adsorptive behaviour of methane on zeolites was investigated at low pressures and it was found that structures and properties play important role in the adsorption of methane. Study results reveal that barium-exchanged zeolite demonstrates a high methane adsorption.